SUSTAINABLE RURAL HOUSING AND THE CHALLENGE OF CLIMATE CHANGE: EXPERIENCES FROM ETHIOPIA - Peter Kellett; Elias Yitbarek Alemayehu (Journal of Architecture&ENVIRONMENT, 2013)
There is now overwhelming evidence that global warming is taking place, but the impacts on the built environment are less effectively documented. Similarly, climate instability is an additional factor in increasing movement of rural populations to ur-ban centres. Inadequate living conditions in rural areas are also recognised as key components in encouraging such migration – hence efforts to create improved rural housing which is sustainable, affordable and desirable is a fundamental challenge. The Ethiopian Institute of Architecture, Building Construction and City Development (EiABC) at Addis Ababa University is committed to developing research and practice into ways of planning and designing housing and settlements to make them more responsive to both to climatic instability and the challenging socio-economic circumstances of Ethiopia. This paper reports on an on-going experimental sustainable rural housing project which is working with local communities to improve traditional vernacular housing through a range of innovative technologies and practices. Following detailed research into local construction technologies and lifestyles, full size prototypes were constructed to explore the positive elements of vernacular architecture within the framework of sustainability, and to test both the technologies and response of residents. This project is one of several live construction projects in the university which is also developing proposals for urban communities. These innovative projects are analysed in the context of climate change responses and sustainable development paradigms.